Qirā’āt, Tafsir, and Legal Reasoning: Reconstructing al-Shāfī‘ī’s Hermeneutical Framework - Zakka, Umar; Wael Hegazy (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2025)
Previous scholarship on al-Shāfī‘ī qirā’āt has largely examined sanad genealogy, the authenticity of Qur’anic readings, and their legal implications as discrete issues, leaving the underlying epistemological coherence insufficiently theorized. This article analyzes the genealogy of al-Shāfī‘ī’s qirā’āt, evaluates their authenticity according to Ibn al-Jazarī’s criteria, and investigates their relationship to tafsīr and legal reasoning through al-Shāṭibī’s coherence theory. Using a historical-analytical approach, it integrates sand analysis, comparative qirā’āt examination, and hermeneutical analysis of representative legal cases. The findings demonstrate that al-Shāfī‘ī was genealogically affiliated with Ibn Kathir’s reading tradition while exercising methodological independence through selected readings shaped by the scholarly traditions of the Hijaz, Basra, and Kufa. Most of the readings underlying his legal arguments are mutawātir, whereas non-canonical reports function primarily as interpretive rather than normative authorities. These findings establish an integrated epistemological framework linking qirā’āt, tafsir, and legal reasoning, thereby advancing Qur’anic Studies and usūl al-fiqh by redefining the role of qirā’āt in classical Islamic legal methodology.